1980
DOI: 10.1126/science.6986656
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Amelogenins in Enameloid of Lower Vertebrate Teeth

Abstract: The indirect method of immunofluorescence was used to demonstrate the presence of amelogenins in the enameloid of teeth and dermal denticles of Chondrichthyes; in the enameloid of Teleostei and Amphibia; and in the enamel of Reptilia. Nonmammalian amelogenins are formed in the ectodermal cells of tooth organs and chemically are so similar to mammalian amelogenins that they interact with antiserum prepared from bovine enamel matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 12 publications
3
32
0
Order By: Relevance
“…The recent progress of light and electron microscopic immunocytochemistry has enabled us to investigate the localization of biological substances with higher resolution and specificity. Using these techniques, the localization of enamel proteins in the tooth system has been studied in a number of disparate vertebrate species at the light microscopic level (GRAVER et al, 1978;HEROLD et al, 1980;SLAVKIN et al, 1982), and in mice and cows at the ultrastructural level (NANCI et al, 1985;HEROLD et al, 1987;SLAVKIN et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The recent progress of light and electron microscopic immunocytochemistry has enabled us to investigate the localization of biological substances with higher resolution and specificity. Using these techniques, the localization of enamel proteins in the tooth system has been studied in a number of disparate vertebrate species at the light microscopic level (GRAVER et al, 1978;HEROLD et al, 1980;SLAVKIN et al, 1982), and in mice and cows at the ultrastructural level (NANCI et al, 1985;HEROLD et al, 1987;SLAVKIN et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Enameloid matrix contains collagen of ectomesenchymal origin and odontoblast cell processes, in addition to ameloblastic cell secretions (primarily enamelin, though amelogenin and other enamel proteins are also present [Herold et al, 1980;Satchell et al, 2002]), and is secreted beneath the basal lamina of the inner dental epithelium (Shellis andMiles, 1974, 1976;Shellis, 1975;Kemp, 1985;Smith, 1995). There is evidence that the shift from enamel to enameloid has occurred on several occasions during vertebrate evolution (Donoghue et al, 2000;Donoghue, 2001).…”
Section: Enameloid Microstructure As a Preadaptation To Crown Group Nmentioning
confidence: 99%
“…Herold and colleagues (1989) suggested that the common ancestral gene for amelogenin appears in the amphibians. Several phylogenetic surveys of amelogeninlike antigens demonstrated immunolocalization within bony and cartilagenous fish, frogs, alligators and mammals (see Herold et al, 1980Herold et al, ,1989Slavkin et al, 1982Slavkin et al, , 1984Slavkin et al, , 1991.…”
Section: Enamel Organ Epithelial Differentiationmentioning
confidence: 97%
“…Both bony and cartilagenous fish teeth have outer tooth coverings that are produced by an inner enamel organ epithelum during the successive stages of tooth morphogenesis (i.e., odontogenic placode, dental lamina, bud, cap, bell, and crown stages of tooth development) (see Shellis, 1975Shellis, , 1978. Within selected samples of bony and cartilagenous fishes tooth covering matrices, both tuftelin and amelogenin antigens have been immunologically identified (see Deutsch et al, 1991;Herold et al, 1980;Slavkin et al, 1982Slavkin et al, , 1984. Curiously, the nondental scales of the dogfish Squalus acanthius contain antigens that are cross-reactive with polyconal antibodies produced against mouse enamel proteins (see .…”
Section: Enamel Organ Epithelial Differentiationmentioning
confidence: 99%